Risk, Causality and Management of Severe Allergic Reactions of RNA Messenger SARS-CoV-2 Vaccine: A Mini Review - Elvira, Dwitya; Raveinal (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
SARS-CoV-2 infection has become a health problem throughout the world, including Indonesia with high rates of morbidity (more than 3 million confirmed case) and mortality (more than 80 thousand) due to COVID-19 since it was announced as pandemic in March 2020. Vaccination is one of the efforts to eliminate the pandemic, and just recently Food and Drug Monitoring Agency (BPOM) and Indonesian Government have granted approval for emergency use of messenger RNA (mRNA)-based vaccines. Allergic reactions after vaccination are rare adverse events, including severe allergic reactions and anaphylaxis. Polyethylene glycol (PEG) in mRNA vaccines is thought to be a hidden allergen that trigger allergies. Screening of individuals with a previous history of allergies is necessary to prevent reaction. Experienced health workers are also needed to provide adequate management in the event of a severe allergic reaction or anaphylaxis after COVID-19 vaccination. Aim of this review is to look at the risk of allergy of mRNA vaccine SARS CoV-2; possible causes of allergies and management of individuals with severe allergies/anaphylaxis.